Construction of Metrotvnews.com Reality: Gibran Rakabuming Raka's Electability Resistance in the Second Debate of 2024 Presidential Candidate and Vice President - Irsyada, Muhamad Ahyan; Istiqomah, Eri (Persepsi: Communication Journal, 2024)
The 2024 presidential election in Indonesia is a pivotal event in the political dynamic that will democratically choose the country's highest leader. According to a survey conducted by Data Indonesia in 2023, Gibran Rakabuming Raka earned a significantly greater level of support, with 56.2%, compared to Muhaimin Iskandar, who only obtained 12.3%. Additionally, Gibran Rakabuming Raka was assessed to have a favorable appearance in the second debate. Although the media's response to the candidates' performance varies, multiple media, such as [Metrotvnews.com] (http://metrotvnews.com/), expressed an unfavorable opinion towards their debate performances. The objective of this research is to reveal the resistance posed by Metrotvnews.com towards the growing popularity of Gibran Rakabuming Raka during the second 2024 Presidential Election debate. The research method used is a descriptive qualitative approach under the constructivist paradigm. The data acquired from news articles published by Metrotvnews.com indicates unfavorable sentiments towards Gibran Rakabuming Raka. The data evaluated utilizing Robert N. Entman's concept of framing analysis consists of four aspects: defining problems, diagnosing causes, making moral judgments, and treatment recommendations. The result of this research indicates that Metrotvnews.com favors Muhaimin Iskandar over Gibran Rakabuming Raka by presenting him negatively. Metrotvnews.com uses expert and practitioner opinions to sway public opinion and conceal its impartiality. Furthermore, it seems that Metrotvnews.com supports Muhaimin Iskandar by creating comparisons between their characters.